Satellite image 1:500 000 Heimefrontfjella, Antarktis ... - Brunk, Karsten (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie) Frankfurt am Main, 1986)
Landsat-1 imagery, supplemented with geographical names, 186/113, 12 December 1972; Annex 11 of 17, Brunk, K. (1986);Scale: 1:500000;Bounding Box: POLYGON ((-11 -73.36, -6.1 -74.31, -9.63 -75.57, -14.5 -74.5, -11 -73.36)) ...